Curb your enthusiasm. The complete eighth season [videorecording (DVD)] - David, Larry; Garlin, Jeff, 1962-; Essman, Susie, 1955- (Home Box Office, 2012)
The series proves how seemingly trivial details of one's day-to-day life, a trip to the grocery store, a remark at a dinner party, a fender-bender, can precipitate a 'Murphy's Law' chain of misfortune to hilarious effect. To keep the narrative spontaneous, Curb is shot without a script; cast members are given scene outlines and often improvise lines as they go.